BACE1 Physiological Functions May Limit Its Use as Therapeutic Target for Alzheimer's Disease. Issue 3 (March 2016) - Barão, Soraia; Moechars, Diederik; Lichtenthaler, Stefan F.; De Strooper, Bart
Abstract : The protease β-site amyloid precursor protein (APP)-cleaving enzyme 1 (BACE1) is required for the production of the amyloid-β (Aβ) peptide, which is central to the pathogenesis of Alzheimer's disease (AD). Chronic inhibition of this protease may temper amyloid production and cure or prevent AD. However, while BACE1 inhibitors are being pushed forward as drug candidates, a remarkable gap in knowledge on the physiological functions of BACE1 and its close homolog BACE2 becomes apparent. Here we discuss the major discoveries of the past 3 years concerning BACE1 biology and to what extent these could limit the use of BACE1 inhibitors in the clinic. Trends: β-Site amyloid precursor protein (APP)-cleaving enzyme 1 (BACE1) has several other substrates besides APP. Bace1 −/− mice display complex cognitive and neurochemical phenotypes. BACE1 has diverse physiological functions beyond APP processing. The physiological functions of BACE1 and its close homolog BACE2 during development and especially in the adult brain remain largely unknown. Several BACE1 inhibitors are currently in advanced phases of clinical trials. All BACE1 inhibitors currently under clinical evaluation also block BACE2. BACE inhibitors for Alzheimer's disease therapy should be monitored with caution and take into consideration potential mechanism-based side effects. If the ongoing clinical trials reveal no major safety issues for the BACE1 compounds, BACE1 inhibition might find a place in the prevention of AD in patients at risk for developing the disease.